What They Think of Us : International Perceptions of the United States since 9/11 - Farber, David, 1956- (Book collections on Project MUSE., 2007)
It has never been more important for Americans to understand why the world both hates and loves the United States. In What They Think of Us, a remarkable group of writers from the Middle East, Europe, Asia, and Latin America describes the world's profoundly ambivalent attitudes toward the United States--before and since 9/11. While many people around the world continue to see the United States as a model despite the Iraq war and the war on terror, the U.S. response to 9/11 has undoubtedly intensified global anti-Americanism. What They Think of Us reveals that substantial goodwill toward America.